Mot1 regulation of promoter binding by TBP varies with stress and gene expression levels independently of coactivator dependence - Priyanka Mittal; Alan G. Hinnebusch (Proceedings of the National Academy of Sciences, 2025)
Mot1 in budding yeast regulates transcription by dissociating general initiation factor TBP (TATA-binding protein) from DNA. Previous studies suggested that Mot1 preferentially removes TBP from stress-responsive promoters containing consensus TATA elements that utilize coactivator SAGA while enhancing TBP binding at “house-keeping” genes with TATA-like elements that employ TFIID for TBP recruitment. In stress conditions of amino acid starvation, by contrast, we found that Mot1 promotes TBP binding at genes activated by transcription factor Gcn4, enriched for TATA/SAGA-dependent promoters, and at SAGA-dependent genes expressed constitutively at high-levels, while suppressing TBP binding at SAGA-dependent genes only expressed at lower levels. Importantly, Mot1’s influence on genes induced by starvation or oxidative stress switches from increased to decreased TBP binding when transcribed at low levels in nonstressed cells. Mot1’s role at TFIID-dependent promoters also scales with transcription level, enhancing TBP binding only for the highly expressed subset. Notably, reduced TBP binding on Mot1 depletion impairs transcription of highly expressed TFIID genes but not highly expressed SAGA/stress-activated genes, suggesting that SAGA produces a surfeit of incomplete preinitiation complexes dependent on Mot1 for assembly.